2020
DOI: 10.1055/s-0040-1722097
|View full text |Cite
|
Sign up to set email alerts
|

Case–Parent Trio Studies in Cleft Lip and Palate

Abstract: Cleft lip with or without cleft palate (CL/P) is one of the most common congenital malformations in humans involving various genetic and environmental risk factors. The prevalence of CL/P varies according to geographical location, ethnicity, race, gender, and socioeconomic status, affecting approximately 1 in 800 live births worldwide. Genetic studies aim to understand the mechanisms contributory to a phenotype by measuring the association between genetic variants and also between genetic variants and phenotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 71 publications
0
6
0
1
Order By: Relevance
“…The caseparent trio study design offers the advantage of testing maternal versus paternal effects, parent of origin effects, and it minimizes issues of confounding that plague traditional case-control designs. 18 Several studies have reported the PAX genes are involved in craniofacial morphogenesis through cellular proliferation, migration, and the regulation of differentiation programs during embryonic development. The paired box 7 (PAX7) gene belong to the PAX gene family and plays a critical role during fetal development as well as in neural crest development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The caseparent trio study design offers the advantage of testing maternal versus paternal effects, parent of origin effects, and it minimizes issues of confounding that plague traditional case-control designs. 18 Several studies have reported the PAX genes are involved in craniofacial morphogenesis through cellular proliferation, migration, and the regulation of differentiation programs during embryonic development. The paired box 7 (PAX7) gene belong to the PAX gene family and plays a critical role during fetal development as well as in neural crest development.…”
Section: Discussionmentioning
confidence: 99%
“…The case–parent trio study design offers the advantage of testing maternal versus paternal effects, parent of origin effects, and it minimizes issues of confounding that plague traditional case–control designs. 18…”
Section: Discussionmentioning
confidence: 99%
“…They are useful for studying the transmission of genetic variants between parents and children and how genetic variants differ between affected and unaffected individuals within a family. 14 The advantages of case-parent trio studies include robustness in sample collection, studying the parent-of-origin (PoO) effects and correct mutations. 15 It is critical to consider the PoO effects 16 while studying craniofacial deformities such as CL/P, where maternal genotype controls the in-utero environment of the developing fetus and separates maternal genotypic effects from imprinting effects.…”
Section: Introductionmentioning
confidence: 99%
“…Alternate to the traditional case–control study is the case-parent trio design in which cleft patient and their parents are analyzed for the genotypes. 13 …”
Section: Introductionmentioning
confidence: 99%